Isolation and characterization of endophytic bacteria from roots of Piper nigrum and their activities against Fusarium oxysporum and Meloidogyne incognita - WIRATNO WIRATNO; MUHAMMAD SYAKIR; IRWANTO SUCIPTO; ANKARDIANSYAH PANDU PRADANA (Society for Indonesian Biodiversity, 2019)
Abstract. Wiratno, Syakir M, Sucipto I, Pradana AP. 2019. Isolation and characterization of endophytic bacteria from roots of Piper nigrum and their activities against Fusarium oxysporum and Meloidogyne incognita. Biodiversitas 20: 682-687. The endophytic bacteria from spices plants have potential as biocontrol agents. Nevertheless, their potential has not been explored. Pepper plant (Piper nigrum L.) is linked with promising endophytic bacteria as biocontrol agents. This study aimed to obtain isolates of endophytic bacteria from root tissues of pepper plant. The isolation of endophytic bacteria was done using surface-sterilization method and using Tryptone Soya Agar (TSA) medium. The result showed that 10 endophytic bacteria were successfully isolated. We found that a total of 9 bacteria were safe for plants and mammals and used for subsequent steps. The selected bacteria showed inhibition activity of Fusarium oxysporum (18.6 to 43.7%). Furthermore, the secondary metabolites of the endophytic bacteria also promoted lethal effects on Meloidogyne incognita (16.6 to 65.8%). The physiological activity also showed that seven isolates were able to produce chitinase, and four (4) isolates were able to produce protease. Additionally, 55.6% of isolates were also able to dissolve phosphorus and fix nitrogen. This study provided fundamental information related to the biocontrol properties of endophytic bacteria isolated from pepper plant roots.